Development of Robust MWCNT Hydrogel Electrochemical Biosensor for Pyocyanin Detection by Phosphotungstic Acid Modification - Ting Xue; Lei Gao; Xianying Dai; Shenhui Ma; Yuyu Bu; Yi Wan (Sensors)
The trace detection of pyocyanin (PCN) is crucial for infection control, and electrochemical sensing technology holds strong potential for application in this field. A pivotal challenge in utilizing carbon materials within electrochemical sensors lies in constructing carbon-based films with robust adhesion. To address this issue, a novel composite hydrogel consisting of multi-walled carbon nanotubes/polyvinyl alcohol/phosphotungstic acid (MWCNTs/PVA/PTA) was proposed in this study, resulting in the preparation of a highly sensitive and stable PCN electrochemical sensor. The sensor is capable of achieving stable and continuous detection of PCN within the range of 5–100 μM across a variety of complex electrolyte environments. The limit of detection (LOD) is as low as 1.67 μM in PBS solution, 2.71 μM in LB broth, and 3.63 μM in artificial saliva. It was demonstrated that the introduction of PTA can complex with PVA through hydrogen bonding to form a stabilized hydrogel architecture, effectively addressing issues related to inadequate film adhesion and unstable sensing characteristics observed with MWCNTs/PVA alone. By adjusting the content of PTA within the hydrogel, an increase followed by a subsequent decrease in sensing current response was observed, elucidating how PTA regulates the active sites and conductive network of MWCNTs on the sensor surface. This study provides a new strategy for constructing stable carbon-based electrochemical sensors and offers feasible assistance towards advancing PCN electrochemical sensors for practical applications.